P300 Using line of sight plots to increase awareness of visibility hazards. (1st September 2016) - Schwabe, Nicholas; Robertson, Ayden; Godwin, Alison
Abstract : Operators of large mobile equipment must contend with limited line of sight (LOS), and must use varying levels of awkward postures to obtain enough LOS to safely manoeuvre in the workplace. Anecdotally, individuals who have never driven large mobile equipment (ie. first responders, supervisors, investigators and other pedestrians) are unaware of the extent of the limited LOS, despite their frequent interactions with such equipment. The safety of pedestrians on worksites hinges on their understanding of the visibility limits of the operators driving around them. Most drivers of passenger cars have an appreciation for their lack of visibility when passing through the blind spots of large transport trucks. This same awareness does not seem to extend to the workplace. A pen and paper test was developed in an effort to assess the mismatch between a pedestrian's perception of equipment LOS and the actual LOS available to the operator. Participants with no previous experience operating large mobile equipment were shown a scaled representation of a haul truck, Euclid EH4500, and were then asked to complete a LOS plot diagram representing the LOS an operator may have, purely based on their interpretation of the external appearance of the equipment. The actual line of sight plot for that machine was then overlaid, and percentage of area overlap was compared to the participants' diagrams. The participants were then given the standard LOS plot, and were given 10 minutes to examine it. Seven days later the participants were asked once again, without any visual aids or reminders of the machine, to draw a LOS plot for the same haul truck. This investigation evaluates the usefulness of LOS plots as a potential low-cost high-impact intervention to increase awareness and knowledge of the health and safety implications of visibility.